On the source of runaway electrons in a pulsed gas discharge; Proceedings of the XXVIIIth International Conference on Phenomenon in Ionized Gases, Prague, july 15-20, 2007 - Mesyats G. A. Gennady Andreyevich (2007, 2007)
В фонде НТБ ТПУ отсутствует